Uptake and translocation of zinc and cadmium by Ricinus communis planted in sewage sludge Contaminated soil - Aziera, Z.N.,; Nik M. Majid, (Penerbit Universiti Kebangsaan Malaysia, 2015)
An estimated 5 million m3 of sewage sludge is produced annually in Malaysia. By 2020 it is expected to increase to 7 million m3. Phytoremediation is a method using plants to reduce soil contamination. An experiment was conducted to evaluate the potential of Ricinus communis as a phytoremediator. A greenhouse study was conducted at Universiti Putra Malaysia. Treatments (soil + sewage sludge) were: T1 (100% soil, control), T2 (25% sewage sludge + 75% soil), T3 (50% sewage sludge + 50% soil), T4 (75% sewage sludge + 25% soil) and T5 (100% sewage sludge). Cd and Zn concentrations were analyzed using atomic absorption spectrophotometer (AAS), texture by the pipette gravimetric method, pH by glass electrode pH meter and total carbon by CHNS analyzer. Cd was highly concentrated in the stems (0.29 ppm) while Zn in the leaves (43.29 ppm). The highest translocation factor for Cd was in treatment T4 (3.53) while for Zn in treatment T3 (2.18). The highest bioconcentration factor of Cd was in treatment T5 (0.21) while treatment T2 for Zn (0.69). This species was able to tolerate and accumulate high concentrations of Cd and Zn and can be used as a potential phytoremediator for sewage sludge contaminated soils to reduce soil pollution.